Penguatan Pemberdayaan Hak Perempuan dan Anak di Desa Tanjung Rambutan - Zulfikar Jayakusuma; Ali Syobri; Balqis Sakinah; Ilma Rama Dona; Jerry Wan Beckam; Annum Satya Rahmah Harahap; Grace Blessinka; Anistasya Febriani; Rizka Azzahra; Indah Apriliani; Celfi Anggryani (Lembaga Pengembangan Kinerja Dosen, 2024)
Women and children are vulnerable to violations of their rights. Therefore, the state through the government must provide efforts to empower the rights of women and children. The role of the government in providing this effort must also be supported by all circles, including students, in providing education and understanding for the parties involved so that the information reaches them. The purpose of this study was to find out how much implementation of efforts to empower women and children's rights has been carried out in Desa Tanjung Rambutan. The method carried out in the study was a quantitative method with filling out a questionnaire survey. The process of data analysis process is carried out by analyzing the responses from the audiences and presenting the data that has been obtained for drawing conclusions.